Yield Gap Analysis of Vegetable Varieties in Kargil District of Jammu and Kashmir - Hussain, Mansoor; Mehdi, Mohd; V R, Renjini; S S, Asha Devi (Indian Journal of Extension Education, 2018)
The study has conducted by Krishi Vigyan Kendra, Kargil in the state Jammu and Kashmir to know about the gaps in  performance of high yielding varieties of vegetables in Front Line Demonstrations and farmers' practices. The  demonstrations were conducted on three vegetable varieties namely Arkel (Pea), Red Coral (Onion) and Mitra (Cabbage)  during the period 2013-14 to 2015-16. The results indicates that adoption of high yielding varieties of vegetables have  increased the production of the vegetables in the district. Also return from the high yielding varieties were high indicating  ample scope for the vegetable growers in the district. The extension gap is found to be higher in all the three varieties. So  there is a need to strengthen the extension approaches to encourage the wider adoption of high yielding varieties so as to  increase the production of vegetables and to reduce the demand- supply gap f the vegetables in the district.
Keywords: Extension gap; front line demonstration; technology gap; yield gap